2022
DOI: 10.1177/23259671221085977
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes After Treatment of Isolated Hidden Meniscal Ramp Lesions

Abstract: Background: Ramp lesions are encountered in 16% to 24% of all anterior cruciate ligament (ACL) ruptures. However, isolated ramp lesions without a ruptured ACL have also been reported. Purpose: To evaluate outcomes after type 3 hidden ramp lesions without ACL rupture were treated with all-inside sutures passed through the standard anterior portal. Study Design: Case series, Level of evidence, 4. Methods: Included were 41 patients (26 female; 63.4%) with isolated type 3 ramp lesions who underwent surgery between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, Karaca et al performed an analysis where they retrospectively evaluated clinical outcomes after repairing type 3 hidden lesions [24]. The authors reported finding an MRI diagnostic sensitivity of 31.7% for this particular type of lesion when comparing MRI findings with direct arthroscopic evaluation [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Karaca et al performed an analysis where they retrospectively evaluated clinical outcomes after repairing type 3 hidden lesions [24]. The authors reported finding an MRI diagnostic sensitivity of 31.7% for this particular type of lesion when comparing MRI findings with direct arthroscopic evaluation [24].…”
Section: Resultsmentioning
confidence: 99%
“…Although Chagas‐Neto et al reported substantial and moderate intraobserver and interobserver agreement of the MRI diagnostic performance for this classification [9], another study reported a high rate of underdiagnosis of RLs (31.6%), with type 3 lesions being the most likely missed lesion (45.9%) on preoperative MRI [46]. Similarly, Karaca et al reported finding a diagnostic sensitivity of only 31.7% for type 3 lesions [24]. Taken together, these studies suggest that MRI may not be a reliable way to assess the different subtypes of RLs.…”
Section: Discussionmentioning
confidence: 99%
“…After the exclusion process detailed in Figure 1 , a total of 32 studies were included in our current concept review. Among these articles, 30 described an all‐inside suture technique [ 2 , 4 , 8 , 9 , 10 , 12 , 16 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 31 , 33 , 35 , 37 , 38 , 39 , 41 , 42 , 43 , 45 , 47 ]. Thirteen of them were related to an all‐inside suture through anterior arthroscopic portals [ 10 , 11 , 14 , 16 , 24 , 25 , 26 , 28 , 31 , 33 , 37 , 38 , 43 , 48 ] while eleven were related to an all‐inside suture through one posteromedial portal [ 4 , 8 , 12 , 16 , 21 , 22 , 41 , 42 , 43 , 44 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among these articles, 30 described an all‐inside suture technique [ 2 , 4 , 8 , 9 , 10 , 12 , 16 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 31 , 33 , 35 , 37 , 38 , 39 , 41 , 42 , 43 , 45 , 47 ]. Thirteen of them were related to an all‐inside suture through anterior arthroscopic portals [ 10 , 11 , 14 , 16 , 24 , 25 , 26 , 28 , 31 , 33 , 37 , 38 , 43 , 48 ] while eleven were related to an all‐inside suture through one posteromedial portal [ 4 , 8 , 12 , 16 , 21 , 22 , 41 , 42 , 43 , 44 , 47 ]. Ten of the all‐inside suture studies through a posteromedial portal described the technique using a hook suture passer device [ 4 , 12 , ...…”
Section: Resultsmentioning
confidence: 99%
“…34 Subsequently, clinical studies investigating the outcome after ACLR and ramp repair reported clinically relevant improvements in postoperative outcome; however, they did not include a control group. 15,22,52 The only randomized controlled trial evaluating repair of RLs versus debridement and trephination of RLs during ACLR showed no significant difference in subjective scores, knee stability, and meniscal healing status with a follow-up of !2 years. 30 However, in this study, only stable RLs were observed.…”
Section: Discussionmentioning
confidence: 99%